A clinical audit of hypomagnesaemia management at Scarborough General Hospital - Dhanushan Gnanendran; Moses Grace Kintu; Aparna Ravikumar; Tadeusz Pawlak (Future Healthcare Journal)
Background: Hypomagnesaemia is a common electrolyte disturbance that can lead to severe complications, including cardiac dysrhythmias and neuromuscular instability. Despite established guidelines by the York and Scarborough Teaching Hospitals NHS Foundation Trust, there is concern that these protocols are not consistently followed, potentially compromising patient outcomes. Objective: This audit aimed to evaluate the management of hypomagnesaemia at Scarborough General Hospital, focusing on adherence to trust guidelines and identifying areas for improvement in clinical practice. Methods: A retrospective analysis was conducted on 98 patients diagnosed with hypomagnesaemia between May and December 2023. Data on patient demographics, severity of hypomagnesaemia, ECG monitoring, treatment modalities and correction times were collected and analysed. The audit compared current practices against trust guidelines, specifically assessing the frequency of ECG monitoring, daily serum magnesium level checks, and the use of parenteral versus oral magnesium supplementation. Results: The audit revealed that 67% of patients had mild, asymptomatic hypomagnesaemia, while 33% presented with moderate to severe forms. ECGs were performed in 66% of cases, with 13.7% showing abnormalities. Despite guidelines recommending daily magnesium level monitoring, only 66% of patients received this care. Severe hypomagnesaemia was corrected within 3.5 days on average, while mild cases required 4.5 days. The frequent use of proton pump inhibitors was identified as a significant contributor to hypomagnesaemia. Notably, only half of the severe cases received the full recommended course of intravenous magnesium sulphate, with many being switched to oral supplementation prematurely. Conclusion: While some aspects of hypomagnesaemia management at Scarborough General Hospital align with trust guidelines, significant gaps remain, particularly in monitoring practices and adherence to treatment protocols. These findings highlight the need for targeted educational initiatives and potential revisions to existing guidelines to improve patient outcomes.